Caracterização do esmalte e dentina humana e de biomateriais a base de fosfato de cálcio para estudos radiológicos - Madelon Aparecida Fernandes (2012)
Experimental and theoretical investigation based on the interaction of radiation with matter, with specific technological and medical applications, presented as objective identification, medical diagnostics, chemical analysis and dosimetry using organic and inorganic materials. In this context, the objective of this study was to determine the dosimetric characteristics of enamel and dentin obtained by two methods of separating structure and different dental biomaterials based calcium phosphate, with intent to obtain a material that simulates the enamel and dentin, in detecting the Xray image diagnosis. As a material and methods, the composition of the enamel and dentin and the biomaterials based on calcium phosphate - Bio-Oss ®, Cerasorb ® M Dental, Straumann ® BoneCeramic and Osteogen ® were determined by the technique of Neutron Activation Analysis (INAA), Elemental Analysis (EA), Mass Spectrometry Inductively Coupled Plasma (ICP/AES) and X-ray Fluorescence (EDX). The same samples were used as attenuators for the measurement of the energy spectrum of X-rays transmitted in qualities RQRs International Electrotechnical Commission (IEC), by means of a spectrometric system comprising the CdTe detector. The mass attenuation coefficient (ì/ñ), the effective atomic number (Zeff) were determined and compared between all the specimens analyzed, using the program WinXCOM; as well the determination and comparison numbers CT performed by Computed Tomography Exam. The results obtained by the techniques of analysis showed that the mineral concentration of the enamel is higher than dentin and elements with a higher concentration Ca and P. In all strains examined was observed that the energy spectrum of X-rays transmitted through the enamel is higher than average power transmitted through the dentin. The ì/ñ of the enamel and dentin specimens decreased with increasing energy. The biomaterials evaluated showed a value closer to the theoretical value when submitted to a higher force condensation.It was observed that the difference between the theoretical and experimental value shows a decreasing behavior in respect to the employed pressure. The biomaterials based calcium phosphate showed the Zeff when compared to the value provided by the program WinXCOM, in the range of voltage of 10 to 200 keV, higher than the enamel and dentin. Among the biomaterials evaluated the Zeff of Ostegen® showed the lowest variation in relation to the Zeff of enamel and dentin. It was observed that measures numbers CT of biomaterials dental relative increased according to the condensing pressures which have been subjected. Their values were closer to enamel and dentin when subjected to a higher condensing pressure. It is concluded according to the methodology employed in this study that the efficiency of analytical techniques to determine elemental human dentin and enamel as well as biomaterials tested, demonstrated the importance of the knowledge of the constituents in the behavior of biomaterials. It also follows that the composition, thickness, uniaxial pressure of samples modified the spectrum, allow comparisons to the theoretical model program WinXCOM, and the biomaterials Osteogen® and Cerasorb M Dental® were closer to the characteristics of dentin and enamel respectively as biomaterials simulators to radiological future studies of these dental structures.